2009
DOI: 10.1088/0256-307x/26/8/082301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Three-Quasiparticle Doublet Bands in 123 I: Possible Evidence of Chirality

Abstract: A new band in the odd proton nucleus 123 I is identified via in-beam 𝛾-ray spectroscopy using the 14 N+ 116 Cd reaction. This band shows up as doublets with the previously assigned πœ‹π‘” 7/2 βŠ— (πœˆβ„Ž 11/2 ) 2 band. Possible configurations of the new band are discussed in the framework of the cranked shell model and the geometrical model. It is argued that the new band might be a chiral partner of the previously known πœ‹π‘” 7/2 βŠ— (πœˆβ„Ž 11/2 ) 2 band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Based on constrained triaxial covariant density functional theory (CDFT) calculations [2], it has been suggested that multiple chiral doublet (MΟ‡ D) bands can exist in a single nucleus [3][4][5][6][7][8]. To date, the chiral doublet bands, including MΟ‡ D bands, have been reported in more than 40 nuclei in the A β‰ˆ 80 [9,10], 100 [11][12][13][14][15][16][17][18], 130 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and 190 [36][37][38][39][40][41][42] mass regions. For details, see recent reviews [43][44][45][46][47][48][49] or data tables [50].…”
mentioning
confidence: 99%
“…Based on constrained triaxial covariant density functional theory (CDFT) calculations [2], it has been suggested that multiple chiral doublet (MΟ‡ D) bands can exist in a single nucleus [3][4][5][6][7][8]. To date, the chiral doublet bands, including MΟ‡ D bands, have been reported in more than 40 nuclei in the A β‰ˆ 80 [9,10], 100 [11][12][13][14][15][16][17][18], 130 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and 190 [36][37][38][39][40][41][42] mass regions. For details, see recent reviews [43][44][45][46][47][48][49] or data tables [50].…”
mentioning
confidence: 99%
“…A pair of positive parity three-quasiparticle band was reported in 123,125 I and was suggested to be associated with the Ο€h 11/2 βŠ— Ξ½(g 7/2 /d 5/2 ) 2 configuration but different deformation [101,102]. In the case of 123 I, the observation of these bands was predicted as the possible evidence of chirality [90]. The reduced transition probabilities, B(M1)/B(E2), are very sensitive to the configurations of the states.…”
Section: Chiral Rotationmentioning
confidence: 95%